2016
DOI: 10.1002/hed.24674
|View full text |Cite
|
Sign up to set email alerts
|

Parotidectomy under sedation and locoregional anesthesia with monitoring of brain activity

Abstract: In selected cases, parotidectomy under sedation plus locoregional anesthesia is feasible and safe. The careful selection of patients and the close collaboration with an anesthesiologist is the key to a successful procedure. © 2016 Wiley Periodicals, Inc. Head Neck 39: 744-747, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…For cases without neck dissection, mean operative time was 89.0 ± 20.4 minutes. This is on par with typical cited operative times for standard parotidectomy [8].…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…For cases without neck dissection, mean operative time was 89.0 ± 20.4 minutes. This is on par with typical cited operative times for standard parotidectomy [8].…”
Section: Resultssupporting
confidence: 57%
“…Additionally, the retrograde technique may be a more expedient technique. A series of 13 patients from Brazil describes parotidectomy under local anesthesia using primarily a classic facial nerve dissection, with identification of the nerve at the tragal pointer and a subsequent anterograde dissection of the branches [8]. Their mean operating time was 118.2 ± 16.4 minutes, compared to this series of 102.8 ± 38.3 minutes (89.0 ± 20.4 minutes when excluding cases with neck dissection).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In Group S, the time of first analgesia request was 10.40 ± 2.41 h. Previous studies using SCPB in parotid surgery did not declare the duration to the first analgesia request [ [1] , [2] , [3] ]. However, Yaho et al [ 27 ] showed that the first analgesic request following SCPB was 18 h in thyroid surgery , as they used higher concentration of LA 10 ml ropivacaine 0.5% [ 27 ].…”
Section: Discussionmentioning
confidence: 96%